The influence of nickel(II) ions in soil on total antioxidant activity and components of the ascorbat-glutathione cycle in transgenic plants Nicotiana tabacum - Pristupa, Kristina V.; Kukulianskaya, Tatsiana A.; Khramtsova, Elena A. (Experimental Biology and Biotechnology, 2022)
We conducted a comparative analysis of some biochemical parameters in non-transgenic and transgenic plants Nicotiana tabacum, cultivated in soil with an increased concentration of nickel(II) ions. Transgenic plants had in their genome a bacterial acdS-gene encoding the 1-aminocyclopropane-1-carboxylate deaminase (ACC-deaminase) enzyme. The introduction of elevated concentrations of nickel ions into the soil promotes induction of the acdS-gene expression and an increase in ACC-deaminase activity in transgenic plants. It was shown that the total antioxidant activity and the content of ascorbic acid, glutathione, ascorbate peroxidase, glutathione peroxidase and glutathione reductase increased in plants under abiotic stress.